Persepsi Klien Perilaku Kekerasan Terhadap Tindakan Restrain Mekanik Di Rsjd Dr. Amino Gondohutomo Propinsi Jawa Tengah - Iswanti, Dwi Indah; Lestari, Sri Puji (Jurnal Keperawatan Jiwa, 2016)
Background: The issue of violent behavior is a mental health problem that is often encountered. In 2013 in a psychiatric hospital Dr. Amino Gondohutomo Central Java province on the total number of mental patients as many as 3914 patients, 39.2% (1534 patients) entered with an indication of violent behavior problems and this number was ranked second largest in the nursing problems experienced by patients. One strategy is being performed on patients curbing violent behavior that includes a crisis management action, binding (restrain) and restriction of movement. Restrain actions impact and varied experience in the client's violent behavior. Objective: To explore patient’s perception to ward mechanical restraint actions to reduce violent behavior, length restraint that experienced by patients, side effects are felt by the patient, restraint effectiveness in reducing violent behavior and security measures restrain the patient. Methods: Qualitative research with phenomenological approach that reveal the depth of experience in action restrain patients. Data were collected by in dept, then the data were analysed and validated using data source triangulation. Result: Mechanical restraint that conducted by the nurses is by binding using rope in wrist and leg’s patients. That length instalation of mechanical restraint are vary depend on the patient’s conditions. Mechanical restraint actions can cause unpleasant side effects, in terms of physical and psychological effects for patients. Mechanical restraints can reduce the violent behavior that is done by the patients. Beside that, the security of mechanical restraints by the patients violent behavior should be done with the proper technique and based on the standard operasional procedures (SOP) in hospital.